Linear accelerator-based radiosurgery is associated with lower incidence of radionecrosis compared with gamma knife for treatment of multiple brain metastases. (June 2020) - Sebastian, Nikhil T.; Glenn, Chase; Hughes, Ryan; Raval, Raju; Chu, Jacqueline; DiCostanzo, Dominic; Bell, Erica H.; Grecula, John; Arnett, Andrea; Gondal, Hasan; McGregor, John; Elder, James B.; et al.
Abstract: Background: Gamma knife (GK) and linear accelerator (LINAC)-based stereotactic radiosurgery (SRS) both offer excellent local control in the management of multiple brain metastases. The efficacy and toxicity of LINAC and GK SRS have not been directly compared in the modern era. We studied outcomes in patients treated with LINAC SRS and GK at two separate institutions. Methods: We identified patients treated with either LINAC or GK who were treated to ≥2 lesions and had available follow up. LINAC patients were treated using single-isocenter multitarget technique. We used Cox regression, Fine and Gray competing risks regression, and nearest neighbor propensity score matching to account for confounders and imbalance between cohorts. Kaplan–Meier curves were used to estimate overall survival and rates of radionecrosis. Results: We identified 391 patients who were treated in 537 courses to a total 2699 lesions (LINAC: 1014, GK: 1685). After propensity score matching, GK was associated with similar overall survival (HR = 0.86; 95% CI 0.59–1.24; p = 0.41) and higher rate of radionecrosis (HR = 3.83; 95% CI 1.66–8.84; p = 0.002) compared to LINAC. In a secondary propensity score matched analysis comparing radionecrosis in single-fraction LINAC and GK, GK remained associated with higher incidence of radionecrosis (HR = 4.42; 95% CI 1.28–15.29; p = 0.019). Conclusions: In this multi-institutional study, we found similar overall survival with lower incidence of radionecrosis in patients treated with LINAC compared to GK SRS. These findings are hypothesis generating and should be validated in an independent cohort.